2016
DOI: 10.1242/jeb.126896
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical responses of rat vibrissae to airflow

Abstract: The survival of many animals depends in part on their ability to sense the flow of the surrounding fluid medium. To date, however, little is known about how terrestrial mammals sense airflow direction or speed. The present work analyzes the mechanical response of isolated rat macrovibrissae (whiskers) to airflow to assess their viability as flow sensors. Results show that the whisker bends primarily in the direction of airflow and vibrates around a new average position at frequencies related to its resonant mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 61 publications
(87 reference statements)
4
56
1
Order By: Relevance
“…Previous work has shown that a whisker both bends and vibrates in response to airflow stimulation (Yu et al, 2016a). Vibrissae-responsive neurons would be expected to respond to both of these mechanical components.…”
Section: Introductionmentioning
confidence: 98%
“…Previous work has shown that a whisker both bends and vibrates in response to airflow stimulation (Yu et al, 2016a). Vibrissae-responsive neurons would be expected to respond to both of these mechanical components.…”
Section: Introductionmentioning
confidence: 98%
“…Although some sensory hairs and hair-like organs that mediate anemotaxis in multiple species have been identified [8][9][10][11], the neural underpinnings of how information about the wind direction is transformed into directional behavioral responses during anemotaxis in the CNS have been understudied.…”
Section: Introductionmentioning
confidence: 99%
“…We also measured the resonant vibrational response of crest feathers for several other types of 342 short peacock feathers (three lengths of peacock mantle feathers, the shortest length of train eyespot feather, and four different body contour feathers), and for one or more crest feathers 344 from four other bird species: two additional species from order Galliformes, the Himalayan monal (Lophophorus impejanus) and the golden pheasant (Chrysolophus pictus); the Victoria 346 crowned pigeon (Goura Victoria) from the order Columbiformes, and the yellow-crested cockatoo (Cacatua sulphurea) from the order Psittaciformes; see S1 Table and S1 The resonant response for each of these feathers was measured for driving forces in the out-ofplane direction for n = 3 trials for each feather at each of two frequency sweep rates (2.0 Hz/s, 0 350 to 120 Hz; 1.33 Hz/s, 0 to 80 Hz); the Himalayan monal sample was also studied using a sweep rate of 0.5 Hz/s over 0 to 30 to reproduce this analysis are available with the data repository for this study [70]. The Nyquist frequency, which gives the upper bound on measurable frequencies [79], was 120 Hz (half the 362 frame capture rate) (> 4× typical biological vibration frequencies used during peafowl displays).…”
Section: Vibrational Dynamics Measurementsmentioning
confidence: 99%
“…A large body of research in mammals and arthropods has 108 found that antennae and sensory hairs play important mechanosensory roles in sound detection; this function is also known to be influenced by their vibrational response and mechanical 110 structures [27,28]. For example, in order for a feather crest to sense environmental airflows, it would need to bend sufficiently to activate mechanosensory nerve cells (P1-P4; Box 1), as has 112 been shown for pigeon covert feathers [2], arthropod sensory hairs, pinniped whiskers, bat sensory hairs, fish lateral line organs [29], and rat whiskers [30,30]. Thus, one would expect 114 crest feathers to be compliant enough to deflect when stimulated by salient airflow stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation